Schistosoma mansoni infection in human and nonhuman primates in selected areas of Oromia Regional State, Ethiopia - Tadesse Kebede; Yohanis Negash; Berhanu Erko (Journal of Vector Borne Diseases, 2018)
Background & objectives: The transmission of schistosomiasis, caused by trematodes of the genus Schistosoma, relies on freshwater snails that act as an intermediate host while human and other mammalian act as the definitive hosts. Many non-human primates (NHPs) such as Chlorocebus aethiops (vervet) and Papio anubis (baboon) are reported to be infected with Schistosoma mansoni in Ethiopia, but the role they play in parasite maintenance and transmission is still not clear. The objective of this study was, therefore, to determine the prevalence of S. mansoni infection in human and NHPs living in close proximities to villages in selected endemic areas of Ethiopia. Methods: In this cross-sectional study, stool specimens were collected from 911 humans, and fresh faecal droppings from 106 NHPs from Bochesa (Ziway), Bishan Gari (Kime) and Finchaa (Camp 7) endemic localities in Oromia Regional State, and examined for S. mansoni and other helminth infections using Kato-Katz method for human participants and direct microscopic examination for NHPs. Results: The prevalence of helminthiasis among the human study population was 42.4% (386/911), and for soil-transmitted helminth infections (A. lumbricoides, hookworms, and T. trichiura) it was 13.4% (122/911). In humans S. mansoni was the predominant parasite, 23.1% (210/911) followed by A. lumbricoides, 8.7% (79/911); hookworms, 5.8% (53/911); T. trichiura, 4.8% (44/911); Taenia species, 2.2% (20/911); E. vermicularis, 2.1% (19/911); and H. nana, 3.2% (29/911). NHPs were found positive for Trichuris species and Strongyloides species besides S. mansoni. Interpretation & conclusion: NHPs might play a significant role in local transmission and maintenance of S. mansoni infection even in the absence of human hosts. This calls for supplementation of chemotherapy for schistosomiasis along with measures such as snail control to interrupt transmission of the disease from humans to NHPs, and vice-versa.